Компьютерное моделирование процесса амортизации с использованием гибридных систем - Томилов И. Н. Иван Николаевич; Достовалов Д. Н. Дмитрий Николаевич; Шальнев Н. Д.; Яковлев В. И. (2016, 2016)
Заглавие с экрана